Association Between Self-Reported Hypertension and Antihypertensive Medication Use and Cardiovascular Disease–Related Events and Expenditures Among Patients Diagnosed With Hypertension. (September 2019) - Baker-Goering, Madeleine M.; Howard, David H.; Will, Julie C.; Beeler Asay, Garrett R.; Roy, Kakoli
Objectives: Research suggests that persons who are aware of the risk factors for cardiovascular disease (CVD) are more likely to engage in healthy behaviors than persons who are not aware of the risk factors. We examined whether patients whose insurance claims included an International Classification of Diseases, Ninth Revision (ICD-9) code associated with hypertension who self-reported high blood pressure were more likely to fill antihypertensive medication prescriptions and less likely to have CVD-related emergency department visits and hospitalizations (hereinafter, CVD-related events) and related medical expenditures than patients with these codes who did not self-report high blood pressure. Methods: We used a large convenience sample from the MarketScan Commercial Database linked with the MarketScan Health Risk Assessment (HRA) Database to identify patients aged 18-64 in the United States whose insurance claims included an ICD-9 code associated with hypertension and who completed an HRA from 2008 through 2012 (n = 111 655). We used multivariate logistic regression analysis to examine the association between self-reported high blood pressure and (1) filling prescriptions for antihypertensive medications and (2) CVD-related events. Because most patients with hypertension will not have a CVD-related event, we used a 2-part model to analyze medical expenditures. The first part estimated the likelihood of a CVD-related event, and the second part estimated expenditures. Results: Patients with an ICD-9 code of hypertension who self-reported high blood pressure had a significantly higher predicted probability of filling antihypertensive medication prescriptions (26.5%; 95% confidence interval, 25.7-27.3; P < .001), had a significantly lower predicted probability of a CVD-related event (0.6%, P < .001), and on average spent significantly less on CVD-related events (251, P = .01) than patients who did not self-report high blood pressure. Conclusion: This study affirms that self-knowledge of high blood pressure, even among patients who are diagnosed and treated for hypertension, can be improved. Interventions that improve patients' awareness of their hypertension may improve antihypertensive medication use and reduce adverse CVD-related events.